Arbitrage of Single Stocks Versus Futures in India: A Case Study - Slivka, Ronald T.; Wu, Jiawei; Shah, Vikram (Indian Journal of Finance, 2012)
Whether for hedging, investing or trading purposes, securities regulators and stock exchanges along with domestic and foreign institutional investors, all have a common interest in having fairly priced futures contracts. Achieving and sustaining fairly valued equity futures depends heavily on the existence of active arbitrage in which stocks and futures are paired off against one another by professional arbitrageurs seeking to exploit any mispricing. Current constraints on efficient arbitrage in India include the high costs of brokerage, government, exchange and regulatory fees, an underdeveloped securities lending business to support short selling and, to a lesser extent, an electronic stock execution platform in need of speedier execution. The result of these costs and constraints is that stock versus futures arbitrage in India is presently confined almost entirely to intraday transactions between selected single stocks and their stock futures contracts. Using recent single stock futures data, this article explores specific arbitrage details of single stocks vs. their futures in the Indian market. The zero arbitrage band width for this type of arbitrage was found to be typically at least twice than that occurring in mature global markets and in serious need of narrowing. If India’s regulators, exchanges and taxing authorities wish to encourage the growth of valuable arbitrage business, then steps will be needed to reduce the costs that widen this band. Knowledge of the requirements for successful arbitrage detailed in this paper can suggest to regulators and exchanges steps necessary for improving market liquidity and increasing participation in India’s rapidly growing stock and futures markets.